2023
DOI: 10.47363/jcet/2023(4)133
|View full text |Cite
|
Sign up to set email alerts
|

Simulate the Dynamic Interactions Across Nutritional Supplements, the Polybiome, and the Biochemical Approach Dependent on Patient-Derived Gastrointestinal Knowledge

Abstract: Dietary and lifestyle planning decisions, dysbiosis in the composition of the microbial community and the production of bioactive metabolites by the gastrointestinal microbiota are all factors that have a significant influence on the mucosal integrity of the intestines and the progression of diseases like colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 246 publications
0
0
0
Order By: Relevance
“…In a study involving the feeding of AGEs to rats, it was found that the rats had an increased incidence of colon tumors [111]. Increased risk of colorectal cancer in the US has been seen due to increased consumption of red and processed meat, according to a prospective cohort study [112]. Japanese study links increased risk of stomach cancer to grilled and barbecued meat consumption.…”
Section: Animal Studiesmentioning
confidence: 99%
“…In a study involving the feeding of AGEs to rats, it was found that the rats had an increased incidence of colon tumors [111]. Increased risk of colorectal cancer in the US has been seen due to increased consumption of red and processed meat, according to a prospective cohort study [112]. Japanese study links increased risk of stomach cancer to grilled and barbecued meat consumption.…”
Section: Animal Studiesmentioning
confidence: 99%